A Spectral Element Implementation for the M3D Extended MHD Code (Communications in Computational Physics, 2008)
A spectral element library has been developed and integrated with the M3Dextended MHD code. The currently used linear triangular finite element implementation and the new high order quadrilateral spectral element implementation are directlycompared on equilibrium, linear stability, and nonlinear evolution calculations run onthe same problems.